Hubungan Logika Hukum dengan Argumentasi Hukum melalui Penalaran Hukum - Misnar Syam; Yasniwati Yasniwati (Nagari Law Review, 2019)
Logic is a thinking activity to do systematic reasoning to produce conclusions which are the art of thinking in a straight, precise and orderly manner. Logical nature is a special nature of law which means that in a reciprocal relationship between legal norms in accordance with the principles of logic. So the relationship between logic and law is from its logical nature which is in accordance with reason. Legal argumentation is the result of legal reasoning. Legal reasoning is the application of principles of right thinking in (logic) in understanding the principles, rules, data, facts and legal propositions. Legal reasoning is derived from logic as a science of valid conclusions from various legal facts, problems, and propositions. Law logic is reasoning to find the legal basis contained in a legal event whether it is a legal act or a violation of law and includes it in a regulation existing law. So the relationship between legal logic and legal arguments is legal arguments based on legal logic.